Respiratory effects of exposure to high levels of particulate among Malaysian traffic police - Mohamad Jamil, Putri Anis Syahira; Mohammad Yusof, Nur Athirah Diyana; Hashim, Nurul Maizura; Karuppiah, Karmegam; Rasdi, Irniza; Mohd Tamrin, Shamsul Bahri; How, Vivien; Sambasivam, Sivasankar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Malaysian traffic police are always working on the public roads to alleviate traffic congestion and therefore exposed them to the polluted air every day. In particular, polluted air containing PM2.5 is dangerous to their respiratory health as they can penetrate deep into the lungs, leading to bronchitis, lung cancer and many more. Hence, this research examined the relationship of personal exposure level to PM2.5 with respiratory symptoms among traffic policemen in Kuala Lumpur and Johor Bahru. Methods: 134 participants among traffic policemen were agreed to participate in this study. They were requested to complete a questionnaire regarding the sociodemographic back-ground and respiratory health information. The questionnaire was adopted from International Union Against Tuberculosis Lung Diseases (1986). Personal exposure level of PM2.5 was measured using an air pump with 5.0μm pore size PVC filter. Results: The mean exposure level of PM2.5 among traffic policemen was 28.69 μg/m3. It was found that some of them possess respiratory symptoms (Coughing 33.6%, Phlegm 25.4%, Wheezing 14.9% and Shortness of breath 32.1%). There was significant association detected at p-value < 0.05 in coughing. Despite, there was no significant association in other symptoms such as phlegm, wheezing and shortness of breath. Conclusions: Traffic police were exposed to a relatively high level of PM2.5 (12.4 μg/m3 to 55.3 μg/m3) and showed symptoms of respiratory effects. Therefore, recognition of the risks connected with occupational lung disease and exposure monitoring must be a high priority. This baseline data can serve as a reference to the top management of traffic police officers in order to develop an occupational safety and health guideline for police officers as required by Occupational Safety and Health Act (OSHA, Act 514 1994).